Application of SCADA System by Using (Fuzzy Logic Controller) on the Cathodic Protection System for Oil Pipelines. - Harbi, Jasim A. (Journal of Petroleum Research and Studies, 2021)
This study is dedicated to design and execute Supervisory Control and Data Acquisition system (SCADA) to monitor and control the corrosion of a pipeline buried under ground. A microcontroller equipped with many sensors and communication system used to control and monitor the process of an impressed current cathodic protection ICCP process for pipeline. The combination of the hardware, was built with LabVIEW and personal computer (PC) interface presents a “SCADA” system for two methods: Fuzzy Logic Controller (FLC) presents closed loop, and a conventional for open loop system. Hence, under temperature of 30°C, an assessment and comparison were carried out for two methods of controls examined at low moisture of soil (50%) and high moisture of soil (80 %) for measuring the potential between pipeline and anode, current, and power. It was found a decrease of (39.7%) in consumed power when the moisture of soil changing from the low to the high level. It was attained that the close loop (FLC) was the best method of performance, and consumption of the power.